In vitro antimicrobial activity of 3,4-dihydro-s-triazinobenzimidazole derivatives - Gulyás, G; Emri, T; Simon, A; Györgydeák, Z (Folia microbiologica, 2002)
Among 31 3,4-dihydro-s-triazinobenzimidazole derivatives tested 12 compounds showed in vitro antimicrobial activity against G+ bacteria. Best results were obtained with substances containing naphthyl or halogenated phenyl group on the triazine ring. The tested derivatives had no significant in vitro antimicrobial activity against either the used G- species or fungi.
Keywords: triaziny; benzimidazoly; houby; Fungi; antiinfekční látky; Triazines; gramnegativní bakterie; Anti-Infective Agents; grampozitivní bakterie; mikrobiální testy citlivosti; Benzimidazoles; Microbial Sensitivity Tests; Gram-Negative Bacteria; antibakteriální látky; Anti-Bacterial Agents; Gram-Positive Bacteria